EVALUATING THE COST-EFFECTIVENESS OF DIFFERENT GROUPS OF HYPERTENSION THERAPY: A PHARMACOECONOMIC STUDY - A, Roobena Parveen; M, Vara Prasanna Rao (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study objective is to evaluate among the different groups of antihypertensive for their cost-effectiveness and to provide information about the effective management of hypertensives both clinically and economically. Methods: This study involves 81 patients aged 18â€“80 years on antihypertensive treatment who were enrolled from December to May with daily dose calculation. It is performed to analyze cost-effectiveness in the management of clinical condition. Data collection form to be entered with age, sex, food habits, occupational status, clinical data, and drugs was used for treatment. Incremental cost-effectiveness ratio is calculated based on the incremental cost for per mmHgâ€ reduction and cost for per patientâ€ reaching target blood pressure (BP). Result: Angiotensin receptor blockers (ARBs) show a significant average reduction of systolic BP (SBP) and beta-blockers (BBs) show an average reduction of diastolic BP (DBP). Angiotensin-converting enzyme inhibitors (ACEIs) are cost effective in SBP and calcium channel blockers are cost effective in maintaining DBP. Conclusion: ARBs, BBs, and ACEIs show the effective management of hypertensives both clinically and economically.